Strategi Meningkatkan Promosi Pelayanan dan Pengelolaan Bengkel AD Motor Sparepart Melalui Media Sosial - Suswandayana, I Kadek Adi; Widanti, Ni Putu Kusuma; Aristana, I Nengah; Juliasa, Made (Synergy and Society Service, 2025)
The community service program has succeeded in significantly improving the performance of AD Motor Sparepart Workshop. Through a more aggressive promotional strategy and optimizing the service system by utilizing modern technology, the workshop has succeeded in attracting more customers, especially for the home service system. In addition, improvements in management, including the use of a more efficient bookkeeping system, have increased overall operational efficiency. Through employee training and development, the workshop team is also able to provide better quality service to customers. Overall, this program has made a positive contribution in strengthening AD Motor Sparepart Workshop's position in the market and is expected to continue to support sustainable business growth.